A fundraising guide for nonprofit board members - Walker, Julia Ingraham (Hoboken, N.J. : Wiley, 2012)
'Everything you need to know as a nonprofit board member to raise more money and help your organization succeed in meeting its goalsEngaging and informative, this practical guide to fundraising contains valuable insights that nonprofit boards need to succeed in raising money in today's dynamic economic environment. While written expressly for board members, this useful handbook also provides advice to executive directors and advancement staff on how to partner with your board to build an unstoppable fundraising team.A Fundraising Guide for Nonprofit Board Members shows you how to raise more money by building board leadership and skills in fundraising. This book covers it all--the board's leadership role in fundraising; how to organize and train your board to raise funds; building a team with board and staff; raising funds for operations, major gifts and capital campaigns; how to ask for gifts; plus a guide for conducting a board retreat that will lead to fundraising success. Demystifies the ask by providing a straightforward guide on how to ask for, and close, gifts Features case studies, real life examples, and checklists in an easy to reference format Offers sample materials for a board retreat on building the successful fundraising team Also by Julia Ingraham Walker: Nonprofit Essentials: Jump-Starting the Stalled Fundraising Campaign Entertaining, practical, and easy to use, this book will become a must-read for all board members, executive directors, and staff who want to build an effective fundraising team'--Provided by publisher.
Includes index.
Keywords: Fund raising; Nonprofit organizations